2020
DOI: 10.1016/j.ajogmf.2020.100214
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrics and gynecology emergency services during the coronavirus disease 2019 pandemic

Abstract: This paper is part of a supplement that represents a collection of COVIDrelated articles selected for publication by the editors of AJOG MFM without additional financial support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 2 publications
1
18
0
2
Order By: Relevance
“…Twenty-five studies [ 13 , 26 , 28 , 29 , 33 , [35] , [36] , [37] , 40 , 42 , [44] , [45] , [46] , [47] , 50 , [56] , [57] , [58] , 60 , [65] , [66] , [67] , [68] , [69] , [70] ] reported on antenatal clinic attendance during the pandemic using a variety of metrics. In several settings, no alteration was made to the standard antenatal care protocol, but decreased antenatal clinic attendance was reported in the majority of studies; in high income settings a decline in face to face contacts was offset by an increase in remote or virtual clinic appointments and the nature but not the number of the appointments varied [ 26 , 29 , 35 , 40 , [42] , [43] , [44] , [45] , 47 , 66 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-five studies [ 13 , 26 , 28 , 29 , 33 , [35] , [36] , [37] , 40 , 42 , [44] , [45] , [46] , [47] , 50 , [56] , [57] , [58] , 60 , [65] , [66] , [67] , [68] , [69] , [70] ] reported on antenatal clinic attendance during the pandemic using a variety of metrics. In several settings, no alteration was made to the standard antenatal care protocol, but decreased antenatal clinic attendance was reported in the majority of studies; in high income settings a decline in face to face contacts was offset by an increase in remote or virtual clinic appointments and the nature but not the number of the appointments varied [ 26 , 29 , 35 , 40 , [42] , [43] , [44] , [45] , 47 , 66 , 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…23,24,31,36,39,68,71 In the two studies that reported the outcome, from Israel and Italy, the associated risk of hospital admission amongst 1042 pregnant women who presented at the emergency department significantly increased, by 214% (pooled RR 1214, 95% CI: 1118–1319, I 2 =0%, P <0.0001) ( Table 4 , Fig. 2 c) [ 68 , 71 ]. Variable results were found in three studies that reported on measures of delay in care-seeking during labour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other nine studies analyzed the issue of the impact of COVID-19 pandemic on the admissions to the A&E unit for obstetrical or gynecological conditions. Two of them were performed in the United States, [ 19 , 20 ] two in Israel, [ 21 , 22 ] one in France, [ 23 ] one in India, [ 24 ] and three in Italy (notably from regions different from ours) [ 25 27 ] (Table 4 ). Only Goyal et al [ 24 ] performed a prospective analysis, while all the others were retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest cohorts were from Abel et al [ 19 ] and Athiel et al [ 23 ] with overall 11,788 and 39,690 patients seen in the period considered, respectively, although it’s worth mentioning that the French study was multicentric. Looking to the period of analysis considered by the various studies, we noticed that Abel et al [ 19 ] compared 3 periods: pre-pandemic, early pandemic and late pandemic; Athiel et al [ 23 ], Goyal et al [ 24 ], Spurlin et al [ 20 ], and Grandi et al [ 26 ] considered the period preceding the pandemic versus the first lockdown period; Kugelman et al [ 22 ] evaluated the month following the pandemic declaration, Salsi et al [ 25 ] assessed the month of March (therefore, immediately before and during the lockdown), and Dell’Utri et al [ 27 ] comprised almost 4 months, from the case of the first COVID-19 affected Italian patient to after the end of the strict lockdown versus the same period of the year 2019; Meyer et al [ 21 ] included two months in their analysis (February and March, which according to what mentioned by Kugelman et al [ 22 ] regarding the first Israeli patient affected means before and immediately after the recognition of SARS-COV-2 diffusion in Israel), comparing to the previous year.…”
Section: Discussionmentioning
confidence: 99%